Entrepreneurial intention in higher education: Evidence of a single-factor structure. - Baistaman, Julaina; Mat Nawi, Farahiyah Akmal; Wan Mustapha, Wan Masnieza; Abu Bakar, Hatinah (Journal of Islamic, Social, Economics and Development, 2025)
Entrepreneurial Intention (EI) is a critical precursor to entrepreneurial behavior, particularly among university students. This study aims to examine the dimensional structure of an adapted EI questionnaire and assess its validity through Exploratory Factor Analysis (EFA). Data were collected from a sample of undergraduate students using a structured EI instrument comprising eight items. A survey with an interval scale between 1 and 10. Preliminary analyses, including the Kaiser-Meyer-Olkin (KMO) measure and Bartlett’s Test of Sphericity, confirmed the suitability of the dataset for EFA. Principal Axis Factoring (PAF) was employed to extract the underlying factor structure. The results revealed a single dominant factor with an eigenvalue greater than 1.0, accounting for 93.8% of the total variance. All items loaded strongly onto this factor, with loadings above 0.9. The internal consistency of the scale was excellent (Cronbach’s alpha = 0.977), confirming the reliability of the unidimensional EI construct in this context. Unlike previous studies that often report multidimensional EI structures, this study confirms the robustness of a unidimensional construct within a homogenous student sample, contributing to the simplification and refinement of EI measurement in similar contexts.